Dynamic scaling exponents of copper electrodeposits from scanning force microscopy imaging : Influence of a thiourea additive on the kinetics of roughening and brightening - Mendez, S. (1998)
Changes in the topography of Cu electrodeposits grown on polycrystalline Cu substrates at low constant current density from still aqueous concentrated CuSO4 + H2SO4 solutions, at 298 K, were studied by scanning force microscopy (SFM) at different scale lengths (L) from the nanometer level upward. The dynamic scaling theory applied to SFM images leads to exponents α = 0.87 ± 0.06 and β = 0.63 ± 0.08, which are consistent with an interface growing under an unstable regime. For similar conditions, the addition of 1,3-diethyl-2-thiourea reduces the average crystal size (〈ds〉) of electrodeposits leading to scaling exponents α = 0.86 ± 0.06 and β = 0.24 ± 0.05 for L < ⟨ds⟩ and a logarithmic dependence for the spatial and temporal evolution of the interface for L > 3 μm and t → 0. In an additive-free plating bath, the unstable growth regime appears to be originated by enhanced electrodeposition at protrusions due to curvature effects and further sustained by the electric and concentration fields built up around the growing deposit. The presence of the additive hinders the development of instabilities driving the evolution of the growing interface to that predicted by the Edwards-Wilkinson growth model on the asymptotic limit.